Crystal structure of the African swine fever virus core shell protein p15 - Kefang Liu; Yumin Meng; Yan Chai; Linjie Li; Huan Sun; George F. Gao; Shuguang Tan; Jianxun Qi (Elsevier, 2021)
African swine fever virus (ASFV) is the causative agent of African swine fever, a highly fatal hemorrhagic disease of pigs, which has resulted in great economic losses to the global pork industry, especially in Asia. ASFV particles are comprised of multiple layers encompassing the genomic DNA. Though the capsid structure has been determined, very little is known about the structure of the core shell. The precursor polyprotein pp62 is the structural component of the core shell that gives rise to the p35 and p15 proteins. Herein, we describe the crystal structure of p15 at a resolution of 2.2 Å. The structure of p15 exhibits as a trimeric conformation that is mainly mediated by intermolecular disulfide bonds and supported by multiple hydrogen bond interactions. The button conformation on the surface of adjacent molecules may also play a role in trimeric formation of the ASFV p15. The center of the p15 trimer exhibits opposite electrostatic characteristics on each side. These findings benefit our understanding of ASFV core shell assembly and will aid in the design of antiviral drugs and vaccines.